2017
DOI: 10.1080/08897077.2016.1275926
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Brief Intervention in High Schools: School Nurses’ Practices and Attitudes in Massachusetts

Abstract: Survey respondents were supportive of universal alcohol screening in school, although few were doing so at the time. When respondents identified students using alcohol, their interventions were closely aligned with clinical recommendations for brief intervention. Implementation of SBIRT that focuses on standardized, annual screening has the potential to deliver high-quality care in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Seventeen studies focused on community and public health under the screenings/referral/follow-up ( n = 12), health education ( n = 2), surveillance ( n = 2) components, and under the overall umbrella of the community/public health principle ( n = 1). The majority of studies included screenings/referrals/follow-up on a variety of topics including anxiety (Allison, Nativio, Mitchell, Ren, & Yuhasz, 2014; Muggeo et al, 2017), body mass index (BMI; Lee & Kubik, 2015; Stalter, Chaudry, & Polivka, 2011), depression (Allison et al, 2014), somatic symptoms (e.g., headache, nausea, and heart racing) and general functioning (home, school, and peers; Muggeo et al, 2017), psychiatric evaluations and referrals to the emergency department (Grudnikoff, Taneli, & Correll, 2015), vision (Kemper, Helfrich, Talbot, & Patel, 2012), hearing (Sekhar et al, 2014), posture (Magee, Kenney, & Mullin, 2012), alcohol use (Lunstead, Weitzman, Kaye, & Levy, 2016), female athlete triad syndrome (Kroshus et al, 2015), acanthosis nigricans (Scott & Hall, 2012), and adolescent dating violence (Khubchandani et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies focused on community and public health under the screenings/referral/follow-up ( n = 12), health education ( n = 2), surveillance ( n = 2) components, and under the overall umbrella of the community/public health principle ( n = 1). The majority of studies included screenings/referrals/follow-up on a variety of topics including anxiety (Allison, Nativio, Mitchell, Ren, & Yuhasz, 2014; Muggeo et al, 2017), body mass index (BMI; Lee & Kubik, 2015; Stalter, Chaudry, & Polivka, 2011), depression (Allison et al, 2014), somatic symptoms (e.g., headache, nausea, and heart racing) and general functioning (home, school, and peers; Muggeo et al, 2017), psychiatric evaluations and referrals to the emergency department (Grudnikoff, Taneli, & Correll, 2015), vision (Kemper, Helfrich, Talbot, & Patel, 2012), hearing (Sekhar et al, 2014), posture (Magee, Kenney, & Mullin, 2012), alcohol use (Lunstead, Weitzman, Kaye, & Levy, 2016), female athlete triad syndrome (Kroshus et al, 2015), acanthosis nigricans (Scott & Hall, 2012), and adolescent dating violence (Khubchandani et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Although not all states have large rural areas and limited access to care, this study applies to at least 18 other states that have a similar percentage of rural area within their borders [ 16 ]. A comprehensive SBIRT model has the potential to address alcohol and other substance use outside of clinical settings, which may be particularly important within rural communities.…”
Section: Discussionmentioning
confidence: 99%
“…SBIRT is most often used in the primary care setting, but the model can be readily adapted to use in community settings. A recent study of high school nurses found that most (64%) reported screening students with suspected substance use and more than 77% of said nurses favored universal alcohol screening in schools [ 16 ]. However, only a minority (18%) of school nurses report using a validated screening tool.…”
Section: Introductionmentioning
confidence: 99%
“…6 In contrast, early risk identification, intervention, and prevention of substance use among adolescents may limit such adverse consequences. 7,8 Internationally, it is reported that healthcare providers can easily fail to detect substance use in adolescents about 75% of the time. 9 Healthcare providers often lack adequate preparation, confidence, and knowledge to identify and manage substance use issues among adolescents, and this may have negative consequences.…”
Section: Introductionmentioning
confidence: 99%